2009
DOI: 10.22347/2175-2753v1i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Educação Não-Formal e o Papel do Educador (a) Social

Abstract: ResumoO presente artigo analisa a participação de segmentos da sociedade civil organizada ao redor de Projetos Sociais Educativos que objetivam a inclusão de comunidades carentes e/ou a promoção do desenvolvimento sustentável, em parceria com diferentes instituições e organizações sociais, inclusive com a rede escolar. Busca-se compreender as ações coletivas no campo da Educação Não-Formal, nos marcos de uma teoria social crítica. As práticas da educação não-formal se desenvolvem usualmente extramuros escolare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
76

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 0 publications
0
7
0
76
Order By: Relevance
“…The results of the present research have indicated that the transversal competences (interpersonal, ethical and esthetical resources) are better developed than As discussed along the sections, the way by which the social educator started at Brazilian NGO was, largely, through non-formal and voluntary work to assist the less favored population (Gohn, 2009). On the other hand the participants from this study in special possess many years of experience in this profession, whose knowledge of practice enabled them to develop the transversal competences, very important for the actuation with children and adolescents from periphery.…”
Section: Final Considerationsmentioning
confidence: 58%
See 3 more Smart Citations
“…The results of the present research have indicated that the transversal competences (interpersonal, ethical and esthetical resources) are better developed than As discussed along the sections, the way by which the social educator started at Brazilian NGO was, largely, through non-formal and voluntary work to assist the less favored population (Gohn, 2009). On the other hand the participants from this study in special possess many years of experience in this profession, whose knowledge of practice enabled them to develop the transversal competences, very important for the actuation with children and adolescents from periphery.…”
Section: Final Considerationsmentioning
confidence: 58%
“…As some of the studies on this worker's history in the country indicate (Dadico, 2003;Gohn, 2006Gohn, , 2009Gohn, , 2011Soares, 2008), the changes in Brazilian education scenario mobilized discussions and debates in relation to these professionals' formation, which are involved in social programs and projects, which involve predominantly the popular society. For this, it is corroborated with a conception of work organization as privileged locus to the complex processes of adult human development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jacobi [5] sugere que o desafio que se coloca à educação ambiental decorre de uma formulação crítica e inovadora em níveis formal e não formal. O nível formal de educação é aquele desenvolvido na escola com conteúdo previamente demarcado, enquanto o não formal consiste nos processos de compartilhamento de experiências, principalmente em espaços e ações coletivas [4].…”
Section: N T R O D U ç ã Ounclassified